Qualitative evaluation of the implementation and national roll-out of the NHS App in England - Claire Reidy; Chrysanthi Papoutsi; Sukriti KC; Bernard Gudgin; Anthony A. Laverty; Felix Greaves; John Powell (BMC Medicine)
Abstract Background The NHS App launched in 2019 as the ‘digital front door’ to the National Health Service in England with core features including General Practitioner (GP) appointment booking, repeat prescriptions, patient access to records and, later on, COVID-19 vaccination certification. Similar patient portals have been adopted in different formats and with variable levels of success. In this longitudinal study (2021–2023) we examined how the NHS App became implemented in the pandemic context and beyond. Methods We recruited 88 participants in 62 qualitative interviews and four focus groups. Participants included patients, carers, members of the public, clinical/non-clinical NHS staff from five GP practices (where we also conducted over 60 h of observations) across England, as well as other industry, policy and civil rights stakeholders. Document analysis also contributed to participant recruitment and data interpretation. Data collection and analysis was informed by the Non-Adoption, Abandonment, Scale-up, Spread and Sustainability (NASSS) framework. Results Our study identified the various ways in which complexity manifested as part of the implementation, use and roll-out of the NHS App. Patients had diverse (positive and negative) user experiences as the app evolved, with some of its features described as more useful than others (e.g. prescription ordering, COVID Pass). As the app primarily provided a gateway to general practice systems and infrastructures, not all features were available by default or consistently to all users, with information often appearing fragmented or system-facing (e.g. coded). NHS staff viewed the app as constituting core NHS infrastructure in the long term which made it appealing, even though initially there was less recognition of its immediate value. There was variable organisational capacity to enable implementation and to put in place processes and staff roles required to support patient adoption. Shifting emphasis towards in-person care, challenges with digital inclusion and controversies related to features such as patient access to own records further complicated roll-out. Conclusions As the NHS App remains a complex innovation in a shifting landscape, it is clear ongoing work is needed to ensure its potential can be sustained to meet patient, service and policy needs. Clinical study registration ISRCTN72729780.